2017
DOI: 10.3847/1538-4365/228/2/13
|View full text |Cite
|
Sign up to set email alerts
|

A Large Catalog of Homogeneous Ultra-Violet/Optical GRB Afterglows: Temporal and Spectral Evolution

Abstract: We present the second Swift Ultra-Violet/Optical Telescope (UVOT) gamma-ray burst (GRB) afterglow catalog, greatly expanding on the first Swift UVOT GRB afterglow catalog. The second catalog is constructed from a database containing over 120, 000 independent UVOT observations of 538 GRBs first detected by Swift, the High Energy Transient Explorer 2 (HETE2), the INTErnational Gamma-Ray Astrophysics Laboratory (INTEGRAL), the Interplanetary Network (IPN), Fermi, and Astro-rivelatore Gamma a Immagini Leggero (AGI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…Wang et al (2013) ferentiated the observed afterglow population by postburst time and light curve morphology, finding apparent magnitude distributions peaking at R = 16.1, 17.3, and 18.4 mag for 100 s, 1000 s, and 3600 s (1 hr) after the burst. Roming et al (2017) report the UVOT magnitudes of the first-observed data point and the afterglow peak as 17.06 and 17.7 mag, respectively. We reproduce these populations in Figure 7, and overplot the TESS 10% photometry limit.…”
Section: Tess and Gamma Ray Burstsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al (2013) ferentiated the observed afterglow population by postburst time and light curve morphology, finding apparent magnitude distributions peaking at R = 16.1, 17.3, and 18.4 mag for 100 s, 1000 s, and 3600 s (1 hr) after the burst. Roming et al (2017) report the UVOT magnitudes of the first-observed data point and the afterglow peak as 17.06 and 17.7 mag, respectively. We reproduce these populations in Figure 7, and overplot the TESS 10% photometry limit.…”
Section: Tess and Gamma Ray Burstsmentioning
confidence: 99%
“…The most recent full catalog of UVOT GRB afterglows (Roming et al 2017) contains 626 total bursts detected by multiple gamma ray missions over six years, of which 538 (86%) were followed up with UVOT. The majority of the remainder were too close to the sun or moon for follow-up, as is the case with GRB 191016A, while a few occurred during instrument downtime.…”
Section: Tess and Gamma Ray Burstsmentioning
confidence: 99%
“…The optical/UV sample consists of 56 long duration GRBs, selected from the second Swift UVOT GRB afterglow catalogue [19], which were observed between April 2005 and December 2010. They were selected using the criteria of [20].…”
Section: Sample Selection and Data Analysismentioning
confidence: 99%
“…With these criteria in mind, we have started with the sample of GRBs studied by Oates et al (2012). The sample of Oates et al (2012) was drawn from the second UVOT GRB catalogue (Roming et al, 2017), which contains all of the GRBs observed with Swift UVOT from the launch of Swift until 25 December 2010. For inclusion in their sample, Oates et al (2012) required that a GRB must have been observed by UVOT within the first 400s after the BAT trigger and have a measurement of redshift, reflecting our criteria (b) and (c).…”
Section: Sample Selectionmentioning
confidence: 99%
“…Oates et al, 2012). The main reason is that photometry derived from the settling exposure is regarded as uncertain because of the changing UVOT photocathode voltage at the beginning of the exposure; the rapidly changing spacecraft attitude can also be a cause for concern (Roming et al, 2017). The settling exposure usually begins 10-15 seconds before the first settled exposure, and so represents a significant shifting forward of the afterglow observations, if the photometry can be trusted.…”
Section: Introductionmentioning
confidence: 99%